(untitled) (Journal of Mathematical Study, 2024)
In this paper, we consider the boundedness and compactness of the multilinear singular integral operator on Morrey spaces, which is defined by T_Af(x)=p.v._R^nΩ(x-y)|x-y|^n+1 R(A;x,y)f(y)dy, where R(A;x,y)=A(x)−A(y)−∇A(y)·(x−y) with D^βA∈BMO(R^n) for all |β|=1. We prove that T_A is bounded and compact on Morrey spaces L^p,λ(R^n) for all 1